The Role of Guanxi and Positive Emotions in Predicting Users’ Likelihood to Click the Like Button on WeChat - Zhao, Haichuan; Zhang, Mingyue (Frontiers in Psychology, 2020)
Clicking the like button is a popularly used interaction function on social media. Although prior empirical studies have examined motives for liking behavior on social media, they have largely neglected culture-driven theories and the underlying mechanisms for why users click the like button. By integrating guanxi theory and the affective response model, we propose a conceptual model to determine what factors influence users' liking behavior on WeChat. We examine data from an online survey of 327 respondents using PLS-SEM. The findings show that content cues (i.e., content usefulness and content interestingness) positively affect WeChat users’ positive emotions, which in turn predict their intention to like. More importantly, guanxi cues (i.e., mianzi giving, renqing, and ganqing) positively affect WeChat users’ expected guanxi benefit, which in turn affects intention to like in two ways. On the one hand, the expected guanxi benefit has a direct positive effect on intention to like; on the other hand, this benefit can translate into positive emotions, which in turn predict users’ intention to like.